Perfusion Scotoma: A Potential Core Underestimation in CT Perfusion in the Delayed Time Window in Patients with Acute Ischemic Stroke - Abrams, K.; Dabus, G. (American Journal of Neuroradiology, 2022)
SUMMARY: With the growing rise in utilization of CT perfusion for selecting patients for thrombectomy in acute ischemic stroke from large vessel occlusion, some potential pitfalls are becoming more commonly seen particularly when it comes to estimating the core infarct size on CT perfusion. Ghost infarct core has been described to account for overestimating core infarct size in the early time period (<3 hours). Herein, we describe the phenomenon of underestimating core infarct size on CT perfusion in the later time period (>6 hours), which we have termed perfusion scotoma.